Are the processes recommended by the NHMRC for improving Cardiac Rehabilitation (CR) for Aboriginal and Torres Strait Islander people being implemented?: an assessment of CR Services across Western Australia - Thompson, Sandra C (BioMed Central, 2009)
BACKGROUND: Cardiovascular disease is the major cause of premature death of Indigenous Australians, and despite evidence that cardiac rehabilitation (CR) and secondary prevention can reduce recurrent disease and deaths, CR uptake is suboptimal. The National Health and Medical Research Council (NHMRC) guidelines Strengthening Cardiac Rehabilitation and Secondary Prevention for Aboriginal and Torres Strait Islander peoples, published in 2005, provide checklists for services to assist them to reduce the service gap for Indigenous people. This study describes health professionals' awareness, implementation, and perspectives of barriers to implementation of these guidelines based on semi-structured interviews conducted between November 2007 and June 2008 with health professionals involved in CR within mainstream health services in Western Australia (WA). Twenty-four health professionals from 17 services (10 rural, 7 metropolitan) listed in the WA Directory of CR services were interviewed. RESULTS: The majority of respondents reported that they were unfamiliar with the NHMRC guidelines and as a consequence implementation of the recommendations was minimal and inconsistently applied. Respondents reported that they provided few in-patient CR-related services to Indigenous patients, services upon discharge were erratic, and they had few Indigenous-specific resources for patients. Issues relating to workforce, cultural competence, and service linkages emerged as having most impact on design and delivery of CR services for Indigenous people in WA. CONCLUSIONS: This study has demonstrated limited awareness and poor implementation in WA of the recommendations of the NHMRC Strengthening Cardiac Rehabilitation and Secondary Prevention for Aboriginal and Torres Strait Islander Peoples: A Guide for Health Professionals. The disproportionate burden of CVD morbidity and mortality among Indigenous Australians mandates urgent attention to this problem and alternative approaches to CR delivery. Dedicated resources and alternative approaches to CR delivery for Indigenous Australians are needed.